A Designing Haji Portion Financing Advertising as a Media Promotion with Direct Marketing Method at Kospin Sekartama - Teguh Setiadi; Abdul Syukur (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
KOSPIN SEKARTAMA is a company engaged in savings and loan services located at Central Main Street No. 141 Weleri Central Java. has several superior products including Multipurpose Loans, and PRIMA Loans (Special Offerings of SEKARTAMA), and also has savings products namely SIMAPAN (Future Savings), and SIMADEB (Future Savings) and has a new product, Haji Portion Financing. The new product is still constrained in the delivery of information because it still uses conventional media which in the present era is deemed ineffective and has less coverage. The problems studied in this design are how to design new media that is more effective and extends its reach. Therefore, the purpose of this design is to produce a financing advertisement for the Haji portion as a promotional medium for KOSPIN SEKARTAMA with the Direct Marketing method and is more focused on online marketing indicators for the application of these advertising products. The design of advertising as a promotional media is expected to be an effective means of promotion and can facilitate communication with the target, namely people who wish to do Haji but have limitations in directly registering for Haji. Keywords: KOSPIN SEKARTAMA, Haji Portion Financing, Advertising, Direct Marketing